2016
DOI: 10.1177/1932296816666537
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Trained Dogs to Alert to Hypoglycemia in Patients With Type 1 Diabetes

Abstract: Background: We examined the reliability of trained dogs to alert to hypoglycemia in individuals with type 1 diabetes. Methods: Patients with type 1 diabetes who currently used diabetes alert dogs participated in this exploratory study. Subjects reported satisfaction, perceived dog glucose sensing ability and reasons for obtaining a trained dog. Reliability of dog alerts was assessed using capillary blood glucose (CBG) and blinded continuous glucose monitoring (CGM) as comparators in 8 subjects (age 4-48). Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 29 publications
0
34
2
Order By: Relevance
“…In fact, our results for hypoglycemia sensitivity during waking hours (35.9% across DADs) were near identical to those reported by Los et al in their study comparing DAD alerts to CGM data (36%). 6 Hyperglycemia sensitivity scores for waking hours were lower than those for hypoglycemia. Although these results replicated our previous finding that DAD accuracy is highly variable across individual dogs, 5 in this study fewer DADs (3/14) performed at levels statistically higher than chance during waking hours.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In fact, our results for hypoglycemia sensitivity during waking hours (35.9% across DADs) were near identical to those reported by Los et al in their study comparing DAD alerts to CGM data (36%). 6 Hyperglycemia sensitivity scores for waking hours were lower than those for hypoglycemia. Although these results replicated our previous finding that DAD accuracy is highly variable across individual dogs, 5 in this study fewer DADs (3/14) performed at levels statistically higher than chance during waking hours.…”
Section: Discussionmentioning
confidence: 91%
“…As a comparative analysis (and as done by Los et al, 2016), 6 we graphed the proportion of DAD alerts at each CGM value, and contrasted this with proportions of all CGM readings at these values (Figure 2). As indicated by higher bars on the graph, DADs alerted more frequently during hypo- and hyperglycemia than would be expected by participants’ total proportion of readings in these ranges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This prompts the patient to test their blood glucose level, and to take appropriate action (e.g., insulin administration or eating) to retain appropriate glucose levels. While some organisations train all dogs to a generic range (see [5]), others train individual dogs to best meet the specific needs of the individual client [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the evidence demonstrating DADs’ ability to accurately detect hypoglycemia is limited and inconclusive, studies indicate that there are positive psychosocial outcomes, including decreased worry [ 49 , 50 ]. The first study to evaluate the objective reliability of DADs in a real-world environment found that despite the 12% positive predictive value, using DADs was feasible and participants were very satisfied with their dog [ 51 ]. One vulnerable population with a long-term health condition that may benefit from AAIs with pet dogs is PLHIV.…”
Section: Introductionmentioning
confidence: 99%